Mechanism of error-free replication across benzo[a]pyrene stereoisomers by Rev1 DNA polymerase - Rechkoblit, Olga (Nat Commun, 2017)
Benzo[a]pyrene (BP) is a carcinogen in cigarette smoke which, after metabolic activation, can react with the exocyclic N (2) amino group of guanine to generate four stereoisomeric BP-N (2)-dG adducts. Rev1 is unique among translesion synthesis DNA polymerases in employing a protein-template-directed mechanism of DNA synthesis opposite undamaged and damaged guanine. Here we report high-resolution structures of yeast Rev1 with three BP-N (2)-dG adducts, namely the 10S (+)-trans-BP-N (2)-dG, 10R (+)-cis-BP-N (2)-dG, and 10S ( − )-cis-BP-N (2)-dG. Surprisingly, in all three structures, the bulky and hydrophobic BP pyrenyl residue is entirely solvent-exposed in the major groove of the DNA. This is very different from the adduct alignments hitherto observed in free or protein-bound DNA. All complexes are well poised for dCTP insertion. Our structures provide a view of cis-BP-N (2)-dG adducts in a DNA polymerase active site, and offer a basis for understanding error-free replication of the BP-derived stereoisomeric guanine adducts.